Molecular markers of aging, exercise capacity, & physical activity in COPD. (October 2021) - Wan, Emily S.; Goldstein, Rebekah L.; Garshick, Eric; DeMeo, Dawn L.; Moy, Marilyn L.
Abstract: Background: Exercise capacity (EC) and physical activity (PA) are independent, potentially modifiable predictors of clinical outcomes in COPD. Molecular measures of biological age may help characterize variability in EC and PA observed among COPD patients. Methods: Veterans with COPD (FEV1 /FVC<0.7 or emphysema on chest computed tomography) enrolled in 2 cohorts at VA Boston completed questionnaires, a 6-min walk distance (6MWD) for EC, and blood collection at enrollment. PA data (average daily step count) was collected using an HJ-720 ITC pedometer over ≥5 days. A subset of subjects returned for repeat assessment after 12 weeks. DNA methylation data was generated using the HumanMethylationEPIC platform; epigenetic estimates of biological age and age acceleration were generated using established algorithms. Multivariable models examined the associations between biological age, 6MWD, PA and future acute exacerbations (AEs), adjusting for chronological age, sex, race, smoking status, pack-years, body mass index, cohort, and estimated cell counts. Results: Subjects (n = 269) were predominantly male (98.5%), white (92.9%), and elderly (70.6 ± 8.5 years) with average FEV1 % of 57.7 ± 21.1, 6MWD of 374.3 ± 93.5 m, and daily steps of 3043.4 ± 2374 at baseline. In adjusted models, multiple measures of baseline epigenetic age and age acceleration were inversely associated with 6MWD; only GrimAge was inversely associated with PA. Longitudinal change in Hannum-Age was inversely associated with change in EC at 12 weeks (n = 94). No measures of biological age were significantly associated with prospective AEs over 1.3 ± 0.3 years. Conclusions: Epigenetic measures of biological age are independent predictors of EC and PA, but not AEs, among individuals with COPD. Highlights: Epigenetic clocks correlate with exercise capacity and physical activity in COPD. Epigenetic age is inversely associated with baseline exercise capacity (6MWD) in COPD. GrimAge is inversely associated with physical activity (average daily step count). Change in Hannum-Age is inversely associated with change in 6MWD at 12 weeks.